Visualization of air and metal inhomogeneities in phantoms irradiated by carbon ion beams using prompt secondary ions - Uhrig, Tanja; Breithaupt, Bernadette; Jäkel, Oliver; Martišíková, Mária (Physica medica, 2017)
Purpose: Non-invasive methods for monitoring of the therapeutic ion beam extension in the patient are desired in order to handle deteriorations of the dose distribution related to changes of the patient geometry. In carbon ion radiotherapy, secondary light ions represent one of potential sources of information about the dose distribution in the irradiated target. The capability to detect range-changing inhomogeneities inside of an otherwise homogeneous phantom, based on single track measurements, is addressed in this paper. Methods: Air and stainless steel inhomogeneities, with PMMA equivalent thickness of 10mm and 4.8mm respectively, were inserted into a PMMA-phantom at different positions in depth. Irradiations of the phantom with therapeutic carbon ion pencil beams were performed at the Heidelberg Ion Beam Therapy Center. Tracks of single secondary ions escaping the phantom under irradiation were detected with a pixelized semiconductor detector Timepix. The statistical relevance of the found differences between the track distributions with and without inhomogeneities was evaluated. Results: Measured shifts of the distal edge and changes in the fragmentation probability make the presence of inhomogeneities inserted into the traversed medium detectable for both, 10mm air cavities and 1mm thick stainless steel. Moreover, the method was shown to be sensitive also on their position in the observed body, even when localized behind the Bragg-peak. Conclusions: The presented results demonstrate experimentally, that the method using distributions of single secondary ion tracks is sensitive to the changes of homogeneity of the traversed material for the studied geometries of the target.